2002
DOI: 10.1063/1.1516234
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric properties of (117)- and (001)-oriented Bi3.25La0.75Ti3O12 polycrystalline thin films

Abstract: Highly (117)- and (001)-oriented Bi3.25La0.75Ti3O12 (BLT) thin films were fabricated on Pt/TiO2/SiO2/Si(100) substrates by chemical solution deposition under the appropriate baking and crystallization conditions. The (117)-oriented BLT films exhibited higher remanent polarization (2Pr=24 μC/cm2), than did (001)-oriented BLT films, which exhibited only a slight amount of polarization (2Pr=6.6 μC/cm2). The results of fatigue and retention tests revealed that neither film was fatigued up to 1×1010 switching cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Nevertheless, most fabricated Bi 4Àx Ln x Ti 3 O 12 thin films were found to have a much smaller remnant polarization (2P r p20 mC/cm 2 ) than expected [1,8]. The small 2P r is owing to that Bi 4Àx Ln x Ti 3 O 12 , commonly made on the Pt electrode, is a polycrystalline film composed predominantly of c-axis-oriented and (1 1 7)-oriented grains, the polar axes of which are either lying almost in the film plane or significantly away from the film normal [9]. To improve the film polarization, it is thus of great interest to design a process that can adjust the crystallization behavior of Bi 4Àx Ln xTi 3 O 12 films to stimulate the growth of a-axisoriented crystals.…”
Section: Introductionmentioning
confidence: 85%
“…Nevertheless, most fabricated Bi 4Àx Ln x Ti 3 O 12 thin films were found to have a much smaller remnant polarization (2P r p20 mC/cm 2 ) than expected [1,8]. The small 2P r is owing to that Bi 4Àx Ln x Ti 3 O 12 , commonly made on the Pt electrode, is a polycrystalline film composed predominantly of c-axis-oriented and (1 1 7)-oriented grains, the polar axes of which are either lying almost in the film plane or significantly away from the film normal [9]. To improve the film polarization, it is thus of great interest to design a process that can adjust the crystallization behavior of Bi 4Àx Ln xTi 3 O 12 films to stimulate the growth of a-axisoriented crystals.…”
Section: Introductionmentioning
confidence: 85%
“…However, the intensity ratio of (0 0 6)/(1 1 7) somewhat increases at a higher dopant concentration, indicating that the doping of Mo and W into BPT films can enhance c-axis-oriented growth. The c-axis-oriented growth can reduce the 2Pr because the BTO phase has a large and a quite small polarization along the a-and c-axes, respectively [32][33][34][35]. SEM observation showed that Moand W-doping induce a reduction in the grain size of BPT films.…”
Section: Article In Pressmentioning
confidence: 99%
“…Recent studies revealed that Bi 3+ ions could also be substituted by other ions such as Nd 3+ , Sm 3+ , Pr 3+ for the improvement of properties [4][5][6]. Among these kinds of doped BTO thin films, Bi 4Àx Nd x TiO 3 [7] has been receiving more attention for its larger remanent polarization than that of Bi 4Àx La x TiO 3 [8], Bi 4Àx Sm x TiO 3 [5], and Bi 4Àx Pr x TiO 3 [6]. low processing temperature below 700 C, which is compatible with Si-based integrated circuit (IC) technology.…”
Section: Introductionmentioning
confidence: 99%